2003
DOI: 10.1677/joe.0.1770057
|View full text |Cite
|
Sign up to set email alerts
|

Specificity of the neuroendocrine response to orgasm during sexual arousal in men

Abstract: We have demonstrated that sexual activity produces transient sympathoadrenal activation and a pronounced, longlasting increase in prolactin in men and women. However, by analyzing endocrine alterations at 10-min intervals, a precise assignment of these changes to the pre-, peri-and postorgasmic periods was not possible. Thus, the current study aimed to accurately differentiate the endocrine response to sexual arousal and orgasm in men using an automatic blood collection technique with 2-min sampling intervals.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
101
0
3

Year Published

2003
2003
2019
2019

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 158 publications
(105 citation statements)
references
References 42 publications
1
101
0
3
Order By: Relevance
“…Mechanistically, this may be related to additional OXT either compensating a relative deficit (optimization hypothesis) or by collapsing already optimal levels (decompensation hypothesis). While the most obvious physiological stimulus for promoting endogenous OXT release in men would be having sex with their mate (Krüger et al, 2003), the simple close presence and touch of their partner at any given moment in time might also suffice (Holt-Lunstad et al, 2008). Thus, OXT effects in promoting monogamy in males may normally depend upon the presence of a close positive relationship in the bond with their female partners and close physical proximity between the couple.…”
Section: Discussionmentioning
confidence: 99%
“…Mechanistically, this may be related to additional OXT either compensating a relative deficit (optimization hypothesis) or by collapsing already optimal levels (decompensation hypothesis). While the most obvious physiological stimulus for promoting endogenous OXT release in men would be having sex with their mate (Krüger et al, 2003), the simple close presence and touch of their partner at any given moment in time might also suffice (Holt-Lunstad et al, 2008). Thus, OXT effects in promoting monogamy in males may normally depend upon the presence of a close positive relationship in the bond with their female partners and close physical proximity between the couple.…”
Section: Discussionmentioning
confidence: 99%
“…It is important to note that our study assessed symptoms occurring post-coitally (with or without experienced orgasm) and not specifically after orgasm, hence do not cover a post-orgasmic condition. Given the hormonal changes that happen at the time of orgasm, which tend to be different from sexual excitement, this could be important (Exton et al, 1999;Krueger et al, 2003). To address this issue we conducted post-hoc analysis using a questionnaire sent to the twins in 2008 and asking about frequency of orgasm during intercourse.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have shown hormonal changes to happen during sexual arousal and orgasm in women and men (Exton et al, 1999;Krueger et al, 2003). In an experimental study conducted on women by Exton et al (1999), film-induced sexual arousal significantly increased plasma adrenaline and noradrenaline concentrations, whereas orgasm induced a large increase in plasma concentrations of prolactin, which remained elevated 60 minutes after completion of arousal.…”
mentioning
confidence: 98%
“…increased for over 1 h following orgasm in men and women, but unchanged following sexual arousal without orgasm (Krüger et al 1998(Krüger et al , 2003M S Exton et al 1999, 2001a, N G Exton et al 2000. Therefore, the present investigation aimed to examine the physiological impact of acute alterations of prolactin on sexual parameters by pharmacological manipulation of prolactin levels in healthy men.…”
Section: Discussionmentioning
confidence: 99%